Examining bank SEOs: Are offers made by undercapitalized banks different? - Krishnan, C.N.V.; Ergungor, O. Emre; Laux, Paul A.; Singh, Ajai K.; Zebedee, Allan A. (Journal of Financial Intermediation, 2010)
Despite extensive monitoring, banking operations are often considered opaque, and despite explicit capital adequacy regulation, banks may have substantial discretion in their financing. Both monitoring and capital regulation have changed substantially over time, with the adoption of FDICIA being one important breakpoint. This article empirically studies seasoned equity offerings (SEOs) by banks to understand how opacity and capital regulation interact to determine the timing of bank SEOs and their market valuation. SEOs both by banks that are undercapitalized relative to regulatory standards and also well-capitalized banks are fully discretionary when it comes to SEOs, even before FDICIA. Both undercapitalized and well-capitalized banks experience similar and significantly negative stock price reactions to SEO announcements, and also have similar prior patterns of insider trading and similar economic drivers of the issuance decision. Moreover, post-SEO abnormal stock returns are similar to benchmark returns for both types of issuers in the long run, suggesting that, contrary to the well-documented evidence for industrial SEOs, investors understand the value implications of bank SEOs upon announcement. The evidence implies that undercapitalized banks' SEOs are more discretionary and that all bank SEOs are less opaque than implied by earlier studies.